Pengaruh Komunikasi Organisasi Terhadap Kinerja Gardener: Studi Kasus The Oberoi Beach and Resort Bali - Aprilia Kusumawardhani, Awanda Vyta; Kohdrata, Naniek; Jelantik, Anak Agung Ayu Wulandira Sawitri (Jurnal Arsitektur Lansekap, 2024)
The Effect of Organization Communication on Gardener Performances: A Case Study at The Oberoi Beach and Resort Bali . This research aims to analyze and describe the significant influence of organizational communication and suitability of organizational communication within The Oberoi Beach and Resort Bali, specifically for the garden maintenance work organizational structure. The population sample in this research were the gardeners at The Oberoi Beach and Resort Bali. The method used in this research is the Partial Least Squares (PLS). As an alternative method of Stuctural Equation Modeling (SEM), the PLS can be used to determine how much the independent variable influence the dependent variable. The result shows that the downward communication significant negatively affect on the gardener performance, however upward communication and horizontal communication show positive significant affect to the gardeners performance.